Enhancement of Lymphangiogenesis by Human Mesenchymal Stem Cell Sheet. Issue 16 (1st July 2022) - Jia, Wenkai; He, Weilue; Wang, Guifang; Goldman, Jeremy; Zhao, Feng
Abstract: Preparation of human mesenchymal stem cell (hMSC) suspension for lymphedema treatment relies on conventional enzymatic digestion methods, which severely disrupts cell–cell and cell–extracellular matrix (ECM) connections, and drastically impairs cell retention and engraftment after transplantation. The objective of the present study is to evaluate the ability of hMSC‐secreted ECM to augment lymphangiogenesis by using an in vitro coculturing model of hMSC sheets with lymphatic endothelial cells (LECs) and an in vivo mouse tail lymphedema model. Results demonstrate that the hMSC‐secreted ECM augments the formation of lymphatic capillary‐like structure by a factor of 1.2–3.6 relative to the hMSC control group, by serving as a prolymphangiogenic growth factor reservoir and facilitating cell regenerative activities. hMSC‐derived ECM enhances MMP‐2 mediated matrix remodeling, increases the synthesis of collagen IV and laminin, and promotes lymphatic microvessel‐like structure formation. The injection of rat MSC sheet fragments into a mouse tail lymphedema model confirms the benefits of the hMSC‐derived ECM by stimulating lymphangiogenesis and wound closure. Abstract : The therapeutic effect of mesenchymal stem cell (MSC) sheets in treating lymphedema is investigated. MSC sheet facilitates lymphatic capillary‐like structure formation both in vitro and in vivo. MSC suspension stimulates lymphangiogenesis and reduces tissue swelling in a mouse tail lymphedema model, while MSC sheet fragments significantly enhance these effects.